Public perceptions, psychological distance and risk communication in the face of climate change: A contextualised review in Peru - Monge Rodríguez, Fredy S. (2021)
Climate change represents a major threat to humanity and it is a matter of concern for the scientific community, society and politicians. The lack of contextual knowledge on risk perception generates a gap between developed and developing countries, being the last ones the most vulnerable to its effects. All this leads us to propose a review study on risk perception, psychological distance and risk communication in the face of climate change, contextualised in Peru. Efforts made by different public institutions and non-governmental organizations are intended for proposing solid programs in the face of climate change. In this context, the support of government policies contextualized in the Peruvian reality is fundamental to put a brake on the increase in temperature and the increase in greenhouse gas emissions. Finally, the paper concludes by indicating the need for interdisciplinary studies that allow for the identification of the importance of the role played by variables such as risk perception, psychological distance and communication strategies in the processes of adaptation and mitigation to climate change.